Implementasi Nilai-Nilai Demokrasi melalui Pembelajaran Pendidikan Kewarganegaraan di MTs Swasta 27 Firdaus - Anisa Amelia Purba; Pawer Erwin Pakpahan; Nur Cahyu Azizah (Departement of Mathematics Education, 2024)
Civic education (Civics) learning is one of the important means in introducing democratic values to the younger generation. This article explains the introduction of how the implementation of democratic values is carried out through Civics learning. Further research is expected to provide deeper insights into the effectiveness of Civics learning in shaping the understanding and practice of democracy among students. This research was conducted with the aim of knowing and analyzing more deeply related to the implementation of democratic values in Civics learning and To find out the form of democratic values in Civics learning Research Method is to use research on research that is descriptive and tends to use process analysis and meaning is more highlighted in qualitative research. The results showed (1) The application of democratic values is carried out by incorporating democratic values in which include tolerance, cooperation, freedom of opinion, mutual respect and confidence. (2) The supporting factors are curriculum, active learning methods, development of thinking skills, teachers. (3) The inhibiting factors are a less supportive curriculum, imbalance of power in the classroom, lack of awareness and understanding. (4) The solution is to instill character in students or students who are democratic, active learning process by involving students directly, developing relevant learning materials.